The Influence Of Accounting Benefits, Individual Benefits, Enterprise Resource Planning (Erp) System Quality And Management Commitment On User Satisfaction - Safitra, Anugra Hana; Pontoh, Grace T; Arif, Hermita (SIMAK, 2024)
This study aims to examine and analyze the influence of accounting benefits, individual benefits, ERP (Enterprise Resource Planning) system quality, and management commitment on user satisfaction in companies located in the City of Makassar that use the ERP system. This research employs a quantitative approach, which emphasizes the analysis of numerical data processed using quantitative research statistical methods with a correlational study approach. The data used in this study is primary data obtained from ERP system users. The data analysis technique used is Structural Equation Modeling (SEM), assisted by Partial Least Squares (PLS) software. The results of this study indicate that accounting benefits, individual benefits, ERP system quality, and management commitment have a positive and significant impact on user satisfaction. This means that, overall, the ERP system is capable of assisting individuals in performing assigned tasks to achieve optimal results.